Stasiun Penumpang Kereta Api Dumai Dengan Pendekatan Arsitektur Kontekstual Kontras - Rifqi, Muhammad Hilman; Hidayat, Wahyu; Djuniati, Sri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Dumai city is one of the cities in Sumatra that traversed by the cross-Sumatra railway track. To accommodate users of railway system, Dumai city requires facilities which is passenger train station. The aim of this research is to produce concept design of train station in Dumai city. The concept applied in this train station design is progressive. The concept of progress is applied to the circulation of buildings with a clear orientation, no user congestion and the formation of physical buildings that show movement images. Main strategies of this design has several aspects such as survey, site analysis, concept, zoning, mass shape, room programing, structure, utility, and facade. Process of train station design emphasis in contextual contrast approach. The contextual approach is applied to the building physic which contrast with its neighbor, but still focus on contextual itself. Finally train station present here will consolidate, save, increase neighbor quality.Key words: Dumai City, Train Station, Contextual Contrast, Neighbors Quality.